Collaboration on Local Wisdom-Based Character Education between Schools and Parents of Students in Islamic Religious Education Units - Kibtiyah, Asriana; Idawati, Khoirotul; Muaz, Yusuf Ahmed (LETIGES, 2025)
This study aims to identify and describe the forms of collaboration between schools and parents in implementing character education for pupils in Years 1 to 3 at the primary education level, also known as the Madrasah Ibtidaiyah. A descriptive qualitative approach was employed using phenomenological methods, enabling an in-depth exploration of the subjective experiences of educational stakeholders. Data were collected through triangulated in-depth interviews, limited participatory observation, and document analysis. The findings reveal that collaboration in character education between madrasahs and parents is dynamic, integrative, and multidimensional, consisting of five key forms: 1) consistent two-way communication serving as an ecological bridge between home and school; 2) participatory parental involvement in school activities as contextual arenas for value socialisation; 3) character value synchronisation through co-developed guidance, establishing a microsystemic moral contract between teachers and parents; 4) integration of local wisdom values such as ojo dumeh, unggah-ungguh, and gotong royong, reinforcing pupils' cultural identity; and 5) character reinforcement through family-based support involving moral rituals, daily habits, and reflective practices at home. The study is limited by its localised context, relatively few participants, and the absence of prolonged observation of home–school interaction. Its original contribution lies in integrating Bronfenbrenner's ecological theory with culturally grounded character education practices and recommending digital and community-based collaborative strategies suitable for primary education settings in Indonesia.